Current prevalence and geographic distribution of helminth infections in the parasitic endemic areas of rural Northeastern Thailand - Pongsakorn Martviset; Wansika Phadungsil; Kesara Na-Bangchang; Wiwat Sungkhabut; Tanutchamon Panupornpong; Parisa Prathaphan; Nattaya Torungkitmangmi; Salisa Chaimon; Chompunoot Wangboon; Mantana Jamklang; Sirilak Chumkiew; Pichanee Watthanasiri; et al. (BMC, 2023)
Abstract Background Helminth infection is a global health issue that not only causes acute helminthiasis but long-term infection may lead to complicated symptoms as well as severe complications. The World Health Organization cooperated with the Ministry of Public Health in many countries, particularly where high prevalence, spending a lot of resources for limiting the infection. In Thailand, the incidence of parasitic helminth infections was continuously declined in the last few decades according to several campaigns for parasitic elimination. However, the rural community in the northeast of Thailand where the highest prevalence of the country still needs to be monitored. This present study aims to report the current prevalence of parasitic helminth infections in Nakhon Ratchasima and Chaiyaphum provinces where sharing a huge area of the northeastern region of Thailand but only a few studies have been published. Methods The stool specimens were collected from 11,196 volunteers and processed by modified Kato-Katz thick smear, PBS-ethyl acetate concentration techniques, and PCR. The epidemiological data were collected, analyzed, and used for generating of parasitic hotspots. Results The results indicated that O. viverrini remains the major parasite in this area with a total prevalence of 5.05% followed by Taenia spp., Hookworms, T. trichiura, and Echinostoma spp., respectively. Mueang district of Chaiyaphum province has the highest prevalence especially O. viverrini with a prevalence of 7.15% that higher than the latest national surveillance. Interestingly, the prevalence of O. viverrini was hugely reported (more than 10%) in five subdistricts. The geographic localization of O. viverrini infections revealed that a lot of water reservoirs such as the lakes or branches of the river in the two-most prevalent subdistricts. Our finding indicated that gender and age were insignificantly different. Conclusion This finding suggested that the parasitic helminth infection in the rural areas of northeast of Thailand remains high and the housing location is a major contributing factor for the parasitic infection.